1997
DOI: 10.1097/00004714-199712000-00002
|View full text |Cite
|
Sign up to set email alerts
|

How Long Should Pindolol Be Associated With Paroxetine to Improve the Antidepressant Response?

Abstract: A double-blind study was undertaken to investigate the period of treatment with the beta-adrenoreceptor/5-hydroxytryptamine 1A (5-HT1A) antagonist pindolol required to enhance the antidepressant effects of paroxetine. After 1 week of a placebo run-in period, 63 untreated major depressive inpatients were randomly assigned to three different groups. Group 1 received paroxetine (20 mg/day) plus placebo (4 weeks). Group 2 received paroxetine (20 mg/day) plus pindolol (7.5 mg/day) for 1 week and placebo for 3 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
71
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(74 citation statements)
references
References 15 publications
2
71
1
Order By: Relevance
“…23, NO. 3 tion of Zanardi et al (1997), that metropolol failed to accelerate the antidepressant response of paroxetine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23, NO. 3 tion of Zanardi et al (1997), that metropolol failed to accelerate the antidepressant response of paroxetine.…”
Section: Discussionmentioning
confidence: 99%
“…* p Ͻ .01, compared to the suppressant effect obtained in rats pre-treated with saline, using a two-way ANOVA. tion of Zanardi et al (1997), that metropolol failed to accelerate the antidepressant response of paroxetine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, such a drug combination may have rapid therapeutic effects that may be detectable during the short-lasting drug withdrawal. Second, the combination of a SSRI with pindolol [antagonist at 5-HT 1A , 5-HT 1B , and ␤ -adrenergic receptors (Assie and Koek 1996;Bourin et al 1998;Gobert and Millan 1999;Hoyer and Schoeffter 1991;Newman-Tancredi et al 1998); also reported to act as a partial agonist at 5-HT 1A and ␣ -adrenergic receptors (Clifford et al 1998;Fornal et al 1999aFornal et al , 1999bFornal et al , 1999cGobert and Millan 1999; Palmier 1994a, 1994b)] accelerates the onset of antidepressant action of SSRIs in humans (Bordet et al 1998;Zanardi et al 1997Zanardi et al , 1998, or augments the antidepressant response to SSRIs in terms of both magnitude and duration of the response (Maes et al 1999;Perez et al 1997;Tome and Isaac 1998; for review, see McAskill et al 1998; however, see Berman et al 1997 however, see Berman et al , 1999Tome et al 1997aTome et al , 1997b. In the present study, instead of pindolol, which has multiple receptor actions, the relatively selective 5-HT 1A receptor antagonist p-MPPI was used.…”
mentioning
confidence: 99%